2017
DOI: 10.24170/8-1-1924
|View full text |Cite
|
Sign up to set email alerts
|

A hidden menace: Cardiovascular disease in South Africa and the costs of an inadequate policy response

Abstract: A hidden menace: Cardiovascular disease in South Africa and the costs of an inadequate policy response and unhealthy diets. Even in rural SA, associated diffusion of urban behaviours is fostering the CVD epidemic. The United Nations projects that the percentage of population above 60 years will more than double between 1999 and 2050 in SA, with the burden due to CVD predicted to become the prime contributor to total morbidity and mortality in the over 50-year age group.(4) However, CVD is taking its toll even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In order to appropriately allocate resources and develop cost-effective therapeutic strategies and programmes for the integrated and simultaneous care of comorbid conditions like HIV infection and hypertension and other NCDs, there is a need to determine the efficiency, quality and acceptability to users, and the effects on health status of integrating care for chronic infections and NCDs [10,15,16]. Therefore, the aim of this study was to evaluate the perceptions and experiences of PLWHIV and hypertension comorbidity on hypertension diagnosis, management and integration within HIV care, and the healthcare providers who deliver such services at ARV clinics in the Western Cape Province of South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…In order to appropriately allocate resources and develop cost-effective therapeutic strategies and programmes for the integrated and simultaneous care of comorbid conditions like HIV infection and hypertension and other NCDs, there is a need to determine the efficiency, quality and acceptability to users, and the effects on health status of integrating care for chronic infections and NCDs [10,15,16]. Therefore, the aim of this study was to evaluate the perceptions and experiences of PLWHIV and hypertension comorbidity on hypertension diagnosis, management and integration within HIV care, and the healthcare providers who deliver such services at ARV clinics in the Western Cape Province of South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates by the World Health Organisation (WHO) using DALYs suggest that NCDs were responsible for 28% of the total burden of disease in South Africa in 2004 [ 3 ]. These conditions are becoming more prevalent with the diffusion of urban lifestyle risk factors, including tobacco smoking, unhealthy diet, alcohol consumption and physical inactivity [ 4 – 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of hypertension, at 20% of the adult population, is of particular concern [ 7 ], with CVD projected to increase by over 40% in the 35–65 years age group by 2030 [ 6 ]. A survey of over 18,000 encounters showed that hypertension follow-up was the leading reason for attending primary care clinics, accounting for 10% of all consultations among adults [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Furthermore, Africa in general, and South Africa specifically, are experiencing an increasing burden of CVD. 2,3 Dyslipidaemia is a major risk factor for atherosclerotic CVD and the primary goal of dyslipidaemia treatment is to reduce levels of low-density lipoprotein cholesterol (LDL-C) to targets recommended by clinical practice guidelines. 4,5 Statins are the preferred choice of lipid-modifying therapy (LMT) because of their proven efficacy and safety, and their relatively low cost.…”
mentioning
confidence: 99%